2011
DOI: 10.1089/neu.2011.1888
|View full text |Cite
|
Sign up to set email alerts
|

Anti-Inflammatory Treatments during the Chronic Phase of Spinal Cord Injury Improve Locomotor Function in Adult Mice

Abstract: Our previous data suggested that ongoing inflammation in the spinal cord 6 weeks following spinal cord injury was detrimental to locomotor function. Others have shown in the acute and sub-acute post-injury phase that microglial/macrophage activation and T regulatory cells are detrimental to recovery. Here, C57BL/6 mice with a moderately severe T9 contusion were injected intravenously daily with minocycline, which reduces microglial/ macrophage activation, or with CD25 antibodies, which reduce T regulatory cell… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
32
0

Year Published

2012
2012
2022
2022

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 41 publications
(32 citation statements)
references
References 49 publications
0
32
0
Order By: Relevance
“…Animal studies have shown that anti-inflammatory treatments significantly ameliorated motor and sensory functional recovery [6973]. Reducing the infiltration of neutrophils, macrophages or T cells with neutralizing antibodies [69, 70], depletion of macrophages [71], or anti-inflammatory cytokine therapy [72] in the acute phase decreased the secondary tissue damage with functional improvement.…”
Section: Reactive Gliosis Following the Cns Injury – From Inflammamentioning
confidence: 99%
See 1 more Smart Citation
“…Animal studies have shown that anti-inflammatory treatments significantly ameliorated motor and sensory functional recovery [6973]. Reducing the infiltration of neutrophils, macrophages or T cells with neutralizing antibodies [69, 70], depletion of macrophages [71], or anti-inflammatory cytokine therapy [72] in the acute phase decreased the secondary tissue damage with functional improvement.…”
Section: Reactive Gliosis Following the Cns Injury – From Inflammamentioning
confidence: 99%
“…Reducing the infiltration of neutrophils, macrophages or T cells with neutralizing antibodies [69, 70], depletion of macrophages [71], or anti-inflammatory cytokine therapy [72] in the acute phase decreased the secondary tissue damage with functional improvement. Repression of microglial/macrophage activation by administration of minocycline or CD25 antibodies during either acute or chronic phases increased the neuroperformance after the traumatic SCI [7375]. Inhibiting the astroglial activation or remodeling the ECM of astrocytic scar enhanced axonal plasticity and regeneration, and promoted the functional improvement in the rodent SCI models [7680].…”
Section: Reactive Gliosis Following the Cns Injury – From Inflammamentioning
confidence: 99%
“…Therefore, 16 articles were identified that met our inclusion criteria. 4,21,29,31,43,45,47,55,62,67,70,75,77,80,84,85 Study Characteristics. The study characteristics are summarized in Table 13; detailed information is available in Table 14.…”
Section: Minocyclinementioning
confidence: 99%
“…Doses of minocycline ranged from 10 to 180 mg/kg; nearly all studies delivered multiple doses of the drug beginning 0-2 hours postinjury and then again every 12-24 hours for 1-6 days. Two studies began minocycline treatment more than 30 days after SCI: Hains et al 31 gave the first injection at 31 days and continued twice a day for 3 days, and Arnold et al 4 gave the first dose at 6 weeks, followed by daily injections for 2 weeks. Teng et al 75 Effectiveness of Therapy.…”
Section: Minocyclinementioning
confidence: 99%
See 1 more Smart Citation